DESKRIPSI RESPON SISWA PADA PEMBELAJARAN DENGAN METODE PROBLEM BASED LEARNING MAUPUN TIDAK MENGGUNAKAN PROBLEM BASED LEARNING - Purwantiningtiyas, Kennia Ayu (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The research, entitled "Student Responses to Learning with Problem Based Learning Methods or Not Using PBL" raises the issue of how students respond to the use of Problem Based Learning models in the Thematic lessons of Elementary School. This study aims to measure the level of student response to thematic subjects using the PBL model at SDN Mojosari. The subjects in this study were grade 4 students at SDN Mojosari, the object of this study was the student's response to the use of the PBL (Problem Based Learning) learning model at SDN Mojosari. In this study, it is discussed about the PBL learning process that educators or teachers must use to change the learning environment unlike in general. Based on the research data, it shows that the use of the PBL ( Problem Based Learning) model is very appropriate when applied in the Thematic learning of Elementary School.